1989
DOI: 10.1128/mcb.9.12.5484
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-mediated regulation of mouse ornithine decarboxylase is posttranslational.

Abstract: The activity of ornithine decarboxylase (ODC) is negatively regulated by intracellular polyamines, which thereby mediate a form of feedback inhibition of the initial enzyme in the pathway of their synthesis. This phenomenon has been believed to result, at least in part, from translational regulation. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 39 publications
8
46
2
Order By: Relevance
“…These secondary structures may negatively affect the translatability of the message and may thus be of regulatory importance [40]. That the ODC mRNA is indeed poorly translated in vivo is indicated by the finding that most of the ODC mRNA is found associated with ribosomal subunits or monosomes [15,41,42]. Only a very small fraction of the ODC mRNA is found in polysomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These secondary structures may negatively affect the translatability of the message and may thus be of regulatory importance [40]. That the ODC mRNA is indeed poorly translated in vivo is indicated by the finding that most of the ODC mRNA is found associated with ribosomal subunits or monosomes [15,41,42]. Only a very small fraction of the ODC mRNA is found in polysomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inhibition of translation by 5' UTR of ODC mRNA has been demonstrated in reticulocyte lysates as well as in cells transfected with various DNA constructs containing the leader sequence [39, 43,441; it is conceivable that this is of importance for the pol yamine-mediated translational control of ODC. However, a study using various DNA constructs has failed to demonstrate such a function [15]. Since at least part of the osmotic control of ODC occurs by a translational mechanism, it appeared of interest to determine whether the 5' UTR may be essential for the hypotonic induction of ODC.…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, it was suggested that histamine and other 1,4-diamines, at micromolar concentrations, mimic the effect of natural polyamines suppressing the ODC induction caused by ornithine in pcrifused Ehrlich ascites tumour cells; these l,&diamines were more effective for ODC induction inhibition than other amines having I ,3-and 1,5-diamine structures [lO,l 11. Multiple mechanisms have been proposed to take place during the ODC feedback regulation by natural polyamines: inhibition of the protein synthesis initiation and/or elongation [5,21], increase in ODC inactivation and/or degradation [6,22], and induction of antizyme [23]. Nevertheless, Kahana and Nathans conclude that these effects are not specific for polyamines, other diamines are also able to mimic natural polyamines inhibiting ODC synthesis [S].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained after inhibition of protein synthesis with cycloheximide do not support an effect of (zh)-chlorpheniramine on ODC degradation. In this sense, chlorpheniramine differs from natural polyamines when used at micromolar range concentration on culture cells [5,6]. However, results obtained from 35S incorporation seem to indicate that chlorpheniramine inhibits the ODC induction by affecting specifically de novo synthesis of the enzyme, as natural polyamines do at translational level [5,8,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation